Effect of transition metal ion doping on photocatalytic properties of In–Ti oxides. Issue 21 (10th November 2015) - Pai, Mrinal Rajesh; Banerjee, Atindra Mohan; Bharadwaj, Shymala Rajkumar
Abstract: Abstract : Nominal compositions of In2 Ti1− x Tm x O5−δ, (0.0 ≤ x ≤ 0.2 and Tm = Fe 3+ and Cr 3+ ) were synthesized by ceramic route and characterized by relevant techniques. In2 Ti1− x Fe x O5−δ samples were single phased isomorphic with In2 TiO5 phase while Cr substitution has resulted in mixed phased compositions. Dynamic light scattering experiments showed the increase in proportion of smaller sized particles with the increase in extent of Fe substitution. Mössbauer spectra revealed that Fe exists in +3 oxidation state in substituted oxides. The band gap decreased from 3.2 (In2 TiO5 ) to 2.1 eV (In2 Ti0.8 Fe0.2 O x −δ ) and to 1.9 eV in case of Cr substitution (In2 Ti0.8 Cr0.2 O5−δ ) attributed to participation of Fe 3 d /Cr 3 d levels. Photocatalytic H2 generation was evaluated over the substituted oxides from water–methanol mixtures under UV–visible irradiation. The decreasing order of photocatalytic activity is as follows: 20% Fe (mol%) > 10% Fe > indium titanate ≈ 20% Cr > 10% Cr. The loading of Pt as cocatalyst on surface of most active photocatalyst, In2 Ti0.8 Fe0.2 O x −δ further enhanced the photocatlytic H2 yield.